FACIES AND ARCHITECTURE OF A SAND-RICH TURBIDITE SYSTEM IN AN EVOLVING COLLISIONAL-TRENCH BASIN: A CASE HISTORY FROM THE UPPER CRETACEOUS-PALAEOCENE GOTTERO SYSTEM (NW APENNINES) (Rivista italiana di Paleontologia e Stratigrafia, 2019)
This study documents the main depositional elements of a dynamically-controlled sand-rich deep-water turbidite system (Upper Cretaceous–Palaeocene Gottero system, north-west Italy). The large exposures and the wide range of facies and deep-water sub-environments recognised, ranging from proximal channels, unconfined proximal and distal lobes and confined basin plain deposits make this an instructive case study to investigate the spatial-temporal relationships between fan features (channels and lobes) and confined to ponded basin-plain deposits developed in a trench-fill basin. The study focus on stratigraphic and palaeo-environmental reconstruction of the Gottero system in the western sector of the basin. Bed types, facies associations and depositional sub-environments are described in main outcrop locations and used to feed a comprehensive bed-scale database. A coherent stratigraphic framework of the system is proposed for the first time, linking its stratigraphic evolution with the collisional-trench context of the Ligurian units during the Upper Cretaceous-Palaeocene. It includes a first stage in which the Gottero was a prograding extensive basin-floor fan developed in a relatively unconfined setting (Gottero 1 and 2), and a second stage in which the system deepens and got progressively confined and segmented in multiple distal depocentres, dominated by sheet-like high magnitude events, meanwhile the proximal area forms a series of fan elements which display an overall retrograding trend (Gottero 3). The basin fill terminates with the deposition of the Giaiette mass-transport complex interepreted to represent the final collapse of the growing Ligurian accrectionary wedge.